Aerodynamic Studies in the Static Components of a Centrifugal Compressor Stage - Reddy, K. Srinivasa; Murty, G.V. Ramana; Sharma, Korada Viswanatha (Faculty Mechanical Engineering, UMP, 2011)
Aerodynamic studies in the static components of a centrifugal compressor stage were conducted using the computational fluid dynamics solver FLUENT. For the simulation study, a typical centrifugal compressor stage geometry with a flow coefficient of 0.053 was chosen, The study is confined to the static components of the centrifugal compressor stage, i.e., the crossover bend (180° U-bend), a radial cascade of return channel vanes, and the exit ducting (90° L-turn). The aerodynamic performance is reported in terms of total pressure loss coefficient, static pressure recovery coefficient, return channel vane surface static pressure distribution, and stage exit swirl angle distribution. The simulated flow through the static components covered five different operating conditions of the actual centrifugal compressor stage: the design point with 100% flow rate, and the off-design operating conditions with 70%, 80%, 110%, and 120% flow rates. The standard k-ε model was used with standard wall functions to predict the turbulence. A minimum total pressure loss coefficient was observed near 80% flow rate when the average flow angle at the U-bend inlet was 24°. Better static pressure recovery was observed with 70%, 80%, and 100% flow rates. The swirl angle distribution at the stage exit was recognized as satisfactory.